Modulatory Effects of the Glucocorticoid and Opioid Systems on Anxiety-Related Behavior in Young and Mature Rats - Kesmati, M.; Rezai, M.; Torabi, M. (Нейрофизиология, 2016)
Considering that there is limited information on interaction between age and effects of the opioid system and glucocorticoids in determination of the level of anxiety, we examined the influences of 1 mg/kg dexamethasone and 20 mg/kg RU486 (as an agonist and an antagonist of glucocorticoid receptors), and also of 5 mg/kg morphine and 20 mg/kg naloxone (as an agonist and an antagonist of the opioid system) on the anxiety level in young and mature male Wistar rats. The percentage of time in the open arms in the plus-maze test was evaluated as an index of anxiety behavior, and the percentage of number of entries in the closed arms was measured as an index of locomotor activity. The results showed that morphine (5 mg/kg) and dexamethasone (1 mg/kg) exerted anxiolytic effects in both young and mature rats, while only in young rats these agents reduced locomotor activity. RU486 could prevent the anxiolytic effect of morphine, and the anxiolytic effect of dexamethasone was inhibited by naloxone in young animals but this was not observed in mature rats. These results showed that there is an interactive effect between glucocorticoids and the opioid system in mediation of anxiety, and the respective events are age-dependent. Враховуючи недостатню інформацію щодо взаємних впливів глюкокортикоїдів та опіоїдної системи на поведінку та залежність відповідних ефектів від віку, ми вивчали впливи введення 1 мг/кг дексаметазону та 20 мг/кг RU486 (агоніста та антагоніста глюкокортикоїдних рецепторів), а також 5 мг/кг морфіну та 20 мг/кг налоксону (агоніста та антагоніста опіоїдної системи) на рівень тривожності в тесті підвищеного лабіринту у молодих та зрілих щурів-самців. Нормовані значення часу, проведеного у відкритих рукавах лабіринту, та аналогічні значення кількості входів до закритих рукавів розглядались як індекси рівня тривожності та інтенсивності локомоторної активності відповідно. Уведення 5 мг/кг морфіну та 1 мг/кг дексаметазону зумовлювали значні анксіолітичні ефекти як у молодих, так і у зрілих щурів; дані агенти істотно знижували локомоторну активність тільки у молодих тварин. RU486 міг усувати анксіолітичні ефекти морфіну. Анксіолітичний вплив дексаметазону гальмувався налоксоном у молодих щурів, але цього не спостерігалось у зрілих тварин. Такі результати свідчать про існування істотної взаємодії глюкокортикоїдів та опіоїдної системи в їх функції опосередкування рівня тривожності та про значну залежність відповідних ефектів від віку.